Particular Forms of Management of Agro – Industrial Complex in the Sustainable Development of Agriculture - AIMURZINA, Baglan; KAMENOVA, Mazken; OMAROVA, Ainura; PESTUNOVA, Galina; KARIPOVA, Ainur; MADENOVA, Kulshara (Journal of Environmental Management and Tourism, 2018)
In this paper it is noted that the important problem of the existing economic relations in the agrarian sphere is the choice of forms of management. The practice of reforms in agriculture has shown that more than 80% of gross output in Kazakhstan is currently produced by "households" and peasant (farmer) farms which provides further increase in the production of agricultural products namely crop production and increase its economic efficiency. Currently the agricultural sector has a tendency to small-scale production. As the situation has shown one of the main factors negatively influencing investment activity is financial instability of the majority of agricultural producers, low level of its profitability and significant risks.  Factors of low profit growth of the agricultural sector are related to the peculiarities of demand for agricultural products and seasonality of production in this industry. The analysis of the structure of gross agricultural production of the Republic of Kazakhstan by categories of farms, the returnability of agricultural production for 2012-2016 shows the impact of the price and yield of grain on the level of farm income. Proposals for further improvement of grain pricing are given.